Two Distinct Stimulus Frequencies Delivered Simultaneously at Low Intensity Generate Robust Locomotor Patterns. Issue 6 (10th March 2016) - Dose, Francesco; Taccola, Giuliano
Abstract : Objectives: Explore the primary characteristics of afferent noisy stimuli, which optimally activate locomotor patterns at low intensity. Materials and Methods: Intracellular and extracellular electrophysiological traces were derived from single motoneurons and from ventral roots, respectively. From these recordings, we obtained noisy stimulating protocols, delivered to a dorsal root (DR) of an isolated neonatal rat spinal cord, while recording fictive locomotion (FL) from ventral roots. Results: We decreased complexity of efficient noisy stimulating protocols down to single cell spikes. Then, we identified four main components within the power spectrum of these signals and used them to construct a basic multifrequency protocol of rectangular impulses, able to induce FL. Further disassembling generated the minimum stimulation paradigm that activated FL, which consisted of a pair of 35 and 172 Hz frequency pulse trains, strongly effective at low intensity when delivered either jointly to one lumbosacral DR or as single simultaneous trains to two distinct DRs. This simplified pulse schedule always activated a locomotor rhythm, even when delivered for a very short time (500 ms). One prerequisite for the two‐frequency protocol to activate FL at low intensity when applied to sacrocaudal afferents was the ability to induce ascending volleys of greater amplitude. Conclusion: Multifrequency protocols can support future studies in defining the most effective characteristics for electrical stimulation to reactivate stepping following motor injury.